2006
DOI: 10.1091/mbc.e04-12-1109
|View full text |Cite
|
Sign up to set email alerts
|

Phosphatase 2A Negatively Regulates Mitotic Exit inSaccharomyces cerevisiae

Abstract: In budding yeast Saccharomyces cerevisiae, Cdc5 kinase is a component of mitotic exit network (MEN), which inactivates cyclin-dependent kinase (CDK) after chromosome segregation. cdc5-1 mutants arrest at telophase at the nonpermissive temperature due to the failure of CDK inactivation. To identify more negative regulators of MEN, we carried out a genetic screen for genes that are toxic to cdc5-1 mutants when overexpressed. Genes that encode the B-regulatory subunit (Cdc55) and the three catalytic subunits (Pph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
90
2
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 70 publications
(97 citation statements)
references
References 43 publications
2
90
2
2
Order By: Relevance
“…In budding yeast, PP2A has also been implicated in regulating mitotic exit and the spindle orientation checkpoint (Queralt et al 2006;Wang and Ng 2006;Chan and Amon 2009). Studies in other systems have reported that some forms of PP2A are inactivated to permit entry into mitosis and that these are important subsequently for mitotic exit (Barr et al 2011).…”
Section: Pp2a and Sin Signalingmentioning
confidence: 99%
“…In budding yeast, PP2A has also been implicated in regulating mitotic exit and the spindle orientation checkpoint (Queralt et al 2006;Wang and Ng 2006;Chan and Amon 2009). Studies in other systems have reported that some forms of PP2A are inactivated to permit entry into mitosis and that these are important subsequently for mitotic exit (Barr et al 2011).…”
Section: Pp2a and Sin Signalingmentioning
confidence: 99%
“…Because the FEAR controls Cdc14 release by inhibiting PP2A Cdc55 (9), the FEAR pathway is hyperactive in cdc55⌬ mutants, wherein the B-regulatory subunit of PP2A is deleted (7,8). To further confirm that CLB5 overexpression is toxic to FEAR mutants, we examined the growth of FEAR mutants overexpressing CLB5 in the absence of Cdc55.…”
Section: Fear Mutants Are More Sensitive To High Levels Of Clb5mentioning
confidence: 99%
“…Nocodazole is a microtubule poison that arrests cells at metaphase with nucleolar localized Cdc14. Deletion of CDC55 results in Cdc14 release in nocodazole-treated cells due to the activation of FEAR (7,8). Cells lacking Bfa1, the negative regulator of MEN, also show released Cdc14 in the presence of nocodazole (17).…”
Section: Released Cdc14 Induced By Fear or Men Does Not Show Substratementioning
confidence: 99%
“…35 However, overexpression of a nondegradable Pds1 does not fully suppress chromatid segregation, suggesting Cdc55 regulates sister chromatid separation independent of Pds1. Cdc55 has been identified as a negative regulator of mitotic exit, 34,36 as it inhibits the release of Cdc14 from the nucleolus into the nucleus, a hallmark event occurring upon activation of the mitotic exit network (MEN). 34,37,38 Cdc55 is required for sister chromatid cohesion in the presence of DNA damage 35 and is involved in Sgo1-dependent meiotic cohesin cleavage through separase regulation.…”
Section: Introductionmentioning
confidence: 99%